PENGARUH POSISI JONGKOK PADA KALA II PERSALINAN (Jurnal Kesehatan Siliwangi, 2022)
The delivery position can increase comfort by stimulating receptors in the brain that decrease the perception of pain due to uterine contractions so can speed up labor. Delivery positions can help the baby move through the pelvis, and some positions increase the diameter of the pelvis. Midwives have an important role in providing support and facilitating mothers to choose a comfortable and appropriate delivery position so as to shorten the length of labor. The squatting position is one of the alternative labor positions that is useful in shortening the length of the second stage of labor. The squat position is categorized as an upright position so that it provides a gravitational force that helps push the lowest part of the fetus down, increases the diameter of the pelvis so that it helps the rotation of the fetus and the mother is free to move and control her weight so that she feels comfortable. This evidence-based case report aims to determine the effect of the squatting position in the second stage of labor on primiparas at UPT Puskesmas Padasuka. Search articles regarding this labor position through Google Scholar, Pubmed and Chocrane Library with the keyword strategy of searching for birth position OR squatting position AND duration of second stage of labor. There were 2 articles that matched the inclusion and exclusion criteria and had been previously screened, then analyzed critically. After critically reviewing the two articles, it is stated important and can be applied to patients. The squatting position was performed by primiparous mothers in the second stage of labor. It was found that the length of the labor stage was 13 minutes, thus the squatting position in the second stage of labor was effective in accelerating labor.